Ökofenac – A more biodegradable alternative to topical diclofenac? - Clemens Woitaske-Proske; Martin Schütt; Alexandra Müller; Björn Raupers; Aaron Beck; Eric Achterberg; Stephan Reichl; Paul M. Jordan; Oliver Werz; Philipp Dahlke; Jonas Bußmann; Friedrich Jurk; et al. (Sustainable Chemistry and Pharmacy, 2026)

Exploiting prior knowledge in continuous decision-making under uncertainty: the case of tennis experts - Damian Beck; Ernst-Joachim Hossner; Stephan Zahno (Experimental Brain Research, 2026)

How many Macropsychanthus (Leguminosae: Papilionoideae) species are found in Bolivia? Clarification of the taxa, a new species and an identification key - Andrés Fonseca-Cortés; Cristiane Snak; Stephan G. Beck; Ruth P. Clark; Bente Klitgaard; Rosember Hurtado Ulloa; Leslie Cayola Perez; Carla Maldonado; Luciano Paganucci de Queiroz (Kew Bulletin, 2025)

Epigenetic age acceleration is a distinctive trait of epithelioid sarcoma with potential therapeutic implications - Simon Haefliger; Olga Chervova; Christopher Davies; Chet Loh; Roberto Tirabosco; Fernanda Amary; Nischalan Pillay; Steve Horvath; Stephan Beck; Adrienne M. Flanagan; Iben Lyskjær (GeroScience, 2024)
Recently, DNA methylation clocks have been proven to be precise age predictors, and the application of these clocks in cancer tissue has revealed a global age acceleration in a majority of cancer subtypes when compared to normal tissue from the same individual. The polycomb repressor complex 2 plays a pivotal role in the aging process, and its targets have been shown to be enriched in CpG sites that gain methylation with age. This complex is further regulated by the chromatin remodeling complex SWItch/Sucrose Non-Fermentable and its core subunit, notably the tumor suppressor gene SMARCB1 , which under physiological conditions inhibits the activity of the polycomb repressor complex 2. Hence, the loss of function of core members of the SWItch/sucrose non-fermentable complex, such as the tumor suppressor gene SMARCB1 , results in increased activity of polycomb repressor complex 2 and interferes with the aging process. SMARCB1 -deficient neoplasms represent a family of rare tumors, including amongst others malignant rhabdoid tumors, atypical teratoid and rhabdoid tumors, and epithelioid sarcomas. As aging pathways have recently been proposed as therapeutic targets for various cancer types, these tumors represent candidates for testing such treatments. Here, by deriving epigenetic age scores from more than 1000 tumor samples, we identified epigenetic age acceleration as a hallmark feature of epithelioid sarcoma. This observation highlights the potential of targeting aging pathways as an innovative treatment approach for patients with epithelioid sarcoma.

A framework for high-fidelity particle tracking on massively parallel systems - Patrick Kopper; Anna Schwarz; Stephen M. Copplestone; Philip Ortwein; Stephan Staudacher; Andrea Beck (Computer Physics Communications, 2023)

Thermal niche traits of high alpine plant species and communities across the tropical Andes and their vulnerability to global warming - Francisco Cuesta; Carolina Tovar; Luis D. Llambí; William D. Gosling; Stephan Halloy; Julieta Carilla; Priscilla Muriel; Rosa I. Meneses; Stephan Beck; Carmen Ulloa Ulloa; Karina Yager; Nikolay Aguirre; et al. (Journal of Biogeography, 2020)
Aim The climate variability hypothesis (CVH) predicts that locations with reduced seasonal temperature variation select for species with narrower thermal ranges. Here we (a) test the CVH by assessing the effect of latitude and elevation on the thermal ranges of Andean vascular plant species and communities, and (b) assess tropical alpine plants vulnerability to warming based on their thermal traits. Location High tropical Andes. Taxon Vascular plants. Methods Temperature data for 505 vascular plant species from alpine communities on 49 summits, were extracted from 29,627 georeferenced occurrences. Species thermal niche traits (TNTs) were estimated using bootstrapping for: minimum temperature, optimum (mean) temperature and breadth (maximum‐minimum). Plant community‐weighted scores were estimated using the TNTs of their constituent species. CVH was tested for species, biogeographical species groups and communities. Vulnerability to global warming was assessed for species, biogeographical species groups and communities. Results Species restricted to the equator showed narrower thermal niche breadth than species whose ranges stretch far from the equator, however, no difference in niche breadth was found across summits’ elevation. Biogeographical species groups distributed close to the equator and restricted to alpine regions showed narrower niche breadth than those with broader ranges. Community‐weighted scores of thermal niche breadth were positively related to distance from equator but not to elevation. Based on their TNTs, species restricted to equatorial latitudes and plant communities dominated by these species were identified as the most vulnerable to the projected 1.5°C warming, due to a potentially higher risk of losing thermal niche space. Main conclusions Our study confirms that the CVH applies to high tropical Andean plant species and communities, where latitude has a strong effect on the thermal niche breadth. TNTs are identified as suitable indicators of species’ vulnerability to warming and are suggested to be included in long‐term biodiversity monitoring in the Andes.

Avoiding a crisis of motivation for ocean management under global environmental change - Peter J. Mumby; James N. Sanchirico; Kenneth Broad; Michael W. Beck; Peter Tyedmers; Megan Morikawa; Thomas A. Okey; Larry B. Crowder; Elizabeth A. Fulton; Denny Kelso; Joanie A. Kleypas; Stephan B. Munch; et al. (Global Change Biology, 2017)
Climate change and ocean acidification are altering marine ecosystems and, from a human perspective, creating both winners and losers. Human responses to these changes are complex, but may result in reduced government investments in regulation, resource management, monitoring and enforcement. Moreover, a lack of peoples’ experience of climate change may drive some towards attributing the symptoms of climate change to more familiar causes such as management failure. Taken together, we anticipate that management could become weaker and less effective as climate change continues. Using diverse case studies, including the decline of coral reefs, coastal defences from flooding, shifting fish stocks and the emergence of new shipping opportunities in the Arctic, we argue that human interests are better served by increased investments in resource management. But greater government investment in management does not simply mean more of “business‐as‐usual.” Management needs to become more flexible, better at anticipating and responding to surprise, and able to facilitate change where it is desirable. A range of technological, economic, communication and governance solutions exists to help transform management. While not all have been tested, judicious application of the most appropriate solutions should help humanity adapt to novel circumstances and seek opportunity where possible.

Functional importance of avian seed dispersers changes in response to human-induced forest edges in tropical seed-dispersal networks - Francisco Saavedra; Isabell Hensen; Stephan G. Beck; Katrin Böhning-Gaese; Denis Lippok; Till Töpfer; Matthias Schleuning (Oecologia, 2014)

High levels of genetic variation at MHC class II DBB loci in the tammar wallaby (Macropus eugenii) - Yuanyuan Cheng; Hannah V. Siddle; Stephan Beck; Mark D. B. Eldridge; Katherine Belov (Immunogenetics, 2009)

The living library of The Cotapata National Park in Bolivia: an example of application of Bolivian law on the access to genetic resources - Lucia Acebey; Amira Apaza; Rosy de Michel; Stephan Beck; Valérie Jullian; Grace Ruiz; Alberto Gimenez; Séverine Chevalley; Michel Sauvain (Biodiversity and Conservation, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Identification of a single killer immunoglobulin-like receptor (KIR) gene in the porcine leukocyte receptor complex on chromosome 6q - Jennifer G. Sambrook; Harminder Sehra; Penny Coggill; Sean Humphray; Sophie Palmer; Sarah Sims; Haru-Hisa Takamatsu; Thomas Wileman; Alan L. Archibald; Stephan Beck (Immunogenetics, 2006)

Chicken TAP genes differ from their human orthologues in locus organisation, size, sequence features and polymorphism - Brian A. Walker; Andrew van Hateren; Sarah Milne; Stephan Beck; Jim Kaufman (Immunogenetics, 2005)

Genomic organization of the HSET locus and the possible association of HLA -linked genes with immotile cilia syndrome (ICS) - Karolina Janitz; Anna Wild; Stephan Beck; S. Savasta; Giampiero Beluffi; A. Ziegler; Armin Volz (Immunogenetics, 1999)